Karakteristik Ibu Kaitannya Dengan Kejadian Bayi Berat Badan Lahir Rendah - Supiati Supiati (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Age, Parity, Incidence of LBW. One indicator to determine the degree of public health is the infant mortality rate (IMR). Infant mortality rate in Indonesia is still relatively high, which recorded 31 per 1,000 live births in 2008. This study aims to determine the relationship between maternal age and parity with LBW in the Maternity Hospital (RB) Juweni Village Pandes Wedi Klaten This study uses descriptive analytic correlation with retrospective approach. The study population all mothers delivered in January 2011-September 2012 with a total population of 142 mothers. The study was conducted in October 2012. The results of the study obtained the highest maternal age age is not at risk of 124 respondents (87.3%), most mothers Parity multi 75 respondents (52.8%), the highest incidence of low birth weight is not 133 respondents (93.7% ). It can be concluded that there is no relationship between the age of mothers with LBW and there is no relationship between the parity of mothers with LBW.